Optimizing clinical outcomes: The journey of twins with CRIM-negative infantile-onset Pompe disease on high-dose enzyme replacement therapy and immunomodulation - Angie H. Fares; Ankit K. Desai; Laura E. Case; Cassie Sharon; Amy Klinepeter; Amelia Kirby; Matthew T. Lisi; Rebecca L. Koch; Priya S. Kishnani (Molecular Genetics and Metabolism Reports)
Infantile-onset Pompe disease (IOPD) is caused by a deficiency in the enzyme acid alpha-glucosidase (GAA). It is characterized by severe and progressive hypertrophic cardiomyopathy and muscle weakness with death in the first 2 years of life if left untreated. Enzyme replacement therapy (ERT) with alglucosidase-alfa is lifesaving, but its effectiveness is influenced by the patient's cross-reactive immunologic material (CRIM) status, dose of ERT, and the development of high antibody titers, which can reduce the therapy's efficacy. The inability of CRIM-negative IOPD patients to produce native GAA exposes them to a high risk of development of anti-rhGAA IgG antibody titers, leading to treatment failure. We present the case of CRIM-negative dizygotic twins treated with high-dose alglucosidase-alfa (40 mg/kg/week), initiated at 28 days (Twin A) and 44 days (Twin B). Both twins received immune tolerance induction (ITI) with rituximab, methotrexate, and IVIG to mitigate antibody response. Initial evaluations revealed elevated left ventricular mass index (LVMI) and elevated biomarkers (urine glucose tetrasaccharide (Glc4), creatine kinase (CK), and aspartate aminotransferase (AST)) in both twins. Following treatment, cardiac function and biomarkers normalized within several months, with a slight delay in Twin B compared to Twin A, likely attributed to the later initiation of ERT. Both twins safely tolerated ITI, achieving immune tolerance with low antibody titers. At 28 months, the twins transitioned to avalglucosidase-alfa (40 mg/kg every other week (EOW)), which was well tolerated without an increase in antibody titers. At 39 months, both twins exhibited normal cardiac function, LVMI, and biomarkers. Motor skills continued to improve, though some kinematic concerns persisted. These cases underscore the importance of early, high-dose ERT combined with ITI in managing CRIM-negative IOPD. While transitioning to avalglucosidase-alfa at 40 mg/kg/EOW was beneficial and well-tolerated in our patients, further studies are needed to confirm its long-term efficacy compared to the high-dose weekly 40 mg/kg alglucosidase-alfa.